2004
DOI: 10.1021/ma0352072
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Organoclay Platelets on Morphology of Nylon-6 and Poly(ethylene-ran-propylene) Rubber Blends

Abstract: The effect of organoclay platelets on morphologies of three blend compositions (80/20, 20/80, and 99.5/0.5 w/w) of nylon-6 (N6) and poly(ethylene-ran-propylene) rubber (EPR) has been studied by scanning and transmission electron micrographs. For the 80/20 (w/w) N6/ERP blend, the dispersed domain size (D) of EPR phase in the N6 matrix decreased significantly even if a small amount of the organoclay was added. The extent of the decrease in D in this blend was similar to N6/EPR blend with an in-situ reactive comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

23
221
1
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 360 publications
(248 citation statements)
references
References 37 publications
23
221
1
3
Order By: Relevance
“…In fact, the incorporation of 30 wt% of cassava starch to a 70:30 PHBV/poly(butylene adipate-coterephthalate) blend led to a higher biodegradation rate without significant changes in mechanical properties [24] . For the 80:20 blend of PHBV with 5 mol% of hydroxyvalerate and high-amylose starch, improvement of compatibilization was achieved during processing with an organic peroxyde [34] . Recently, some results were published concerning the role of clay minerals nanoparticules as compatibilizing and reinforcing agents for some immiscible synthetic polymer blends, when located at the interface or within the continuous phase [34][35][36][37][38] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the incorporation of 30 wt% of cassava starch to a 70:30 PHBV/poly(butylene adipate-coterephthalate) blend led to a higher biodegradation rate without significant changes in mechanical properties [24] . For the 80:20 blend of PHBV with 5 mol% of hydroxyvalerate and high-amylose starch, improvement of compatibilization was achieved during processing with an organic peroxyde [34] . Recently, some results were published concerning the role of clay minerals nanoparticules as compatibilizing and reinforcing agents for some immiscible synthetic polymer blends, when located at the interface or within the continuous phase [34][35][36][37][38] .…”
Section: Introductionmentioning
confidence: 99%
“…For the 80:20 blend of PHBV with 5 mol% of hydroxyvalerate and high-amylose starch, improvement of compatibilization was achieved during processing with an organic peroxyde [34] . Recently, some results were published concerning the role of clay minerals nanoparticules as compatibilizing and reinforcing agents for some immiscible synthetic polymer blends, when located at the interface or within the continuous phase [34][35][36][37][38] . Considering the favorable interactions between starch and montmorillonites [39][40][41] , the objective of this work was to investigate the properties of 1:1 PHBV and regular cornstarch blend nanocomposites, prepared by melt-extrusion in the presence of increasing contents of an organicallymodified montmorillonite.…”
Section: Introductionmentioning
confidence: 99%
“…They revealed that this blend is immiscible but only one T g was observed due to the close proximity of individual T g 's of both PBS and PBAT. Other reports have shown that OMMT can act as compatibilizer for immiscible polymer blends [9][10][11][12][13][14][15] which exhibit remarkable improvement in their properties compared to the pristine polymer or the conventional composite [16,17]. The interlayer cations between the silicate layers such as Na + are exchanged with organic cations to increase the organonophilicity of the clay layers.…”
Section: Introductionmentioning
confidence: 99%
“…A lot of studies have been done on the influence of organo-clay on polymer blends [17][18][19][20][21] . These studies have shown the organoclay may reside preferable within the bulk of the better compatible polymer, might also become localized at the interfacial region as well.…”
Section: Introductionmentioning
confidence: 99%